Women Seafarer Indecision: Staying or Leaving? - Hermawati , Renny; Dwiatmadja, Christantius; Sugiarto, Agus; Suharti, Lieli (Journal of Ecohumanism, 2024)
The phenomenon of hidden discrimination practices in the recruitment of women seafarers, limited social interaction, and negative perceptions lead to hesitation to stay or leave their profession. The study examines various factors that are suspected to play a role in the decisions of women seafarers, as well as the meaning of state of well-being that they want. The study uses a qualitative case study approach, with a comparative interview technique on women seafarers who stay and who leave their jobs. The results of the study show that there are differences in the factors behind the decisions of women seafarers to stay and those who leave the profession. Differences in perspectives in the meaning of state of well-being were also found in this study.